Trajetórias afro-brasileiras na arquitetura nigeriana do século XIX - Silva, Wellington Conegundes da [UNIFESP] (2020)
This dissertation focuses on the study of Brazilian-style architecture that took place in the city of Lagos, Nigeria, during the 19th and early 20th centuries, in particular, the Shitta Bey mosque. The temple is an important testimony of the relationship between Brazil-Africa, and of the cultural aspects between traditions that took place in the black diasporas over the Atlantic (from slavery to the return of the agudás), starting with the Portuguese expansionism that took place since the 15 thcentury. The proposition of these studies references the historiography of Brazilian architecture, which disregards the creative participation of black culture, that is well represented in this Nigerian architecture. This story took place through transcultural relations of the return of the populations of freed people (forras) and their descendants to the so-called Yorubaland, which corresponds mainly to the territories occupied by the Yoruba nations in Nigeria. Thus, in the years 1820 and 1870, these returned Afro-Brazilians participated in the process of Nigerian modernization, a time when English colonialism took place in the city of Lagos. In the new order, Afro-Brazilian returnees introduced a series of technical advancements and contributed to changes in customs. Brazilian-style architecture emerged within an identity pattern of Afro-Brazilians, as their art had a strong link with colonial architecture, especially between the 18th and 19th centuries (particularly n Bahia). For the returnees, it was a training that took place on the construction site and also through the importation of aesthetic standards, which served to differentiate them from other social groups, as well as motivating them to seek rebirth under signs of prestige that had re-signified the relationships the relationships of to slave exploitation. Thus, the Shitta Bey Mosque sums up a strategy of placing itself between two worlds, that is, in it we can identify the diacritical signs that present different aspects of Bahia and the Yoruba crossing. And the Brazilian aspects of the returnees are configured mainly around religious syncretism’s, which seem to be a territory of permanence, which are of great value for new historiographical perspectives on Brazilian’s.